Ponovna najdba podvrste Anophthalmus micklitzi staudacheri Müller, 1923 (Coleoptera: Carabidae: Trechinae) - Kofler, Bojan (Acta entomologica slovenica (Ljubljana), 2011)
After destruction of its natural habitat in the cave Tular (Cad. No.: 369) in the town Kranj (Slovenia) the subspecies Anophthalmus micklitzi staudacheri disappeared from the type locality. During long-term intensive research in morphologically, hydrologically and geologically similar caves in the vicinity of this cave, author found it again in 2002.
Keywords: Anophthalmus micklitzi staudacheri; Carabidae; Coleoptera; hrošči; Slovenia; Slovenija; Trechinae